2018
DOI: 10.1016/j.sedgeo.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and tectonic setting of Carboniferous–Triassic sandstones from the Karaburun Peninsula, western Turkey: A multi-method approach with implications for the Palaeotethys evolution

Abstract: Carboniferous-Triassic siliciclastic sediments of the Karaburun Peninsula in western Turkey were studied to unravel their provenance and the tectonic setting of depositional basins within the Palaeotethyan realm. A set of complementary techniques including petrography, bulk-rock geochemistry and single-grain analysis of rutile, garnet and chrome spinel were applied to provide a diverse dataset for testing existing palaeotectonic models using both, established and recently published diagrams. We show that tecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Nevertheless, a considerable amount (up to 25%) of high-temperature rutiles in the Dikendağı Formation implies the existence of high-grade (granulite-facies) rocks in the source area. In terms of source rock composition, detrital rutiles from the Upper Palaeozoic rocks of Karaburun were (with few exceptions) dominantly derived from felsic lithologies, which is also recorded by grains from the Permian-Carboniferous and Permian-Triassic units of Chios (Meinhold et al 2008a;Löwen et al 2018). Despite the many similarities, detrital garnet and Cr-spinel do only occur in the Chios-Karaburun units, while they are virtually absent in studied rocks from the Konya Complex.…”
Section: Comparable Unitsmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, a considerable amount (up to 25%) of high-temperature rutiles in the Dikendağı Formation implies the existence of high-grade (granulite-facies) rocks in the source area. In terms of source rock composition, detrital rutiles from the Upper Palaeozoic rocks of Karaburun were (with few exceptions) dominantly derived from felsic lithologies, which is also recorded by grains from the Permian-Carboniferous and Permian-Triassic units of Chios (Meinhold et al 2008a;Löwen et al 2018). Despite the many similarities, detrital garnet and Cr-spinel do only occur in the Chios-Karaburun units, while they are virtually absent in studied rocks from the Konya Complex.…”
Section: Comparable Unitsmentioning
confidence: 94%
“…Previously, the tectono-stratigraphic similarities of the Chios, Karaburun and Konya units were used as strong arguments to correlate these units and interpret them as different parts of the same active continental margin (Robertson and Ustaömer 2009b). Essential provenance data to test if this correlation is viable were scarce but were provided over the last years for both, Chios and Karaburun (Meinhold et al 2007(Meinhold et al , 2008aLöwen et al 2017Löwen et al , 2018. These studies have identified lowgrade metamorphosed sedimentary rocks as major sources but locally also recognized high proportions of (sub)angular grains derived from a felsic volcanic source that was interpreted as an indication for the presence of a relatively proximal continental-arc.…”
Section: Comparable Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…10). Continental eolian sediments (CB) are from the Older and Lower Red Sandstones from England (Hillier et al, 2006) and from the Tarim Basin, China (Rittner et al, 2016) and Turkey (Löwen et al, 2018). They are characterised by a relative abundance of quartz, with few micas, but K-feldspars.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The large-ion lithophile elements (LILEs) (Rb, Ba, Sr, Th, U) are compared to the UCC, in which Sr (61.4-375 ppm) and Rb (22.3-108.5 ppm) are depleted with minor enrichment of Th (2.12-12.65 ppm) in sandstone samples (Figure 7a). Incompatible and easily mobilized LILE concentrations are usually controlled by the existence/ lack of feldspar, and LILEs show enrichment in the UCC compared with the mantle (Löwen et al, 2018). The incompatible high field-strength elements (HFSEs) are considered to be relatively immobile elements and thus could give additional information for the provenance of the sedimentary rocks (Taylor and McLennan, 1985).…”
Section: Major and Trace Elementsmentioning
confidence: 99%